2020
DOI: 10.3390/biom10040564
|View full text |Cite
|
Sign up to set email alerts
|

Tetrameric Structures of Inorganic CBS-Pyrophosphatases from Various Bacterial Species Revealed by Small-Angle X-ray Scattering in Solution

Abstract: Quaternary structure of CBS-pyrophosphatases (CBS-PPases), which belong to the PPases of family II, plays an important role in their function ensuring cooperative behavior of the enzymes. Despite an intensive research, high resolution structures of the full-length CBS-PPases are not yet available making it difficult to determine the signal transmission path from the regulatory to the active center. In the present work, small-angle X-ray scattering (SAXS) combined with size-exclusion chromatography was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…These complications can be softened by the use of small angle x-ray scattering (SAXS) (Skar-Gislinge et al, 2010;Berthaud et al, 2012;Kynde et al, 2014;Dadinova et al, 2020), which, despite that it only provides a resolution down to about 10 Å, allows one to study complex biological samples directly in solution. Moreover, in recent years, nanodiscs (NDs), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These complications can be softened by the use of small angle x-ray scattering (SAXS) (Skar-Gislinge et al, 2010;Berthaud et al, 2012;Kynde et al, 2014;Dadinova et al, 2020), which, despite that it only provides a resolution down to about 10 Å, allows one to study complex biological samples directly in solution. Moreover, in recent years, nanodiscs (NDs), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These complications can be softened by the use of small angle x-ray scattering (SAXS) (Skar-Gislinge et al, 2010;Berthaud et al, 2012;Kynde et al, 2014;Dadinova et al, 2020), which, despite that it only provides a resolution down to about 10Å, allows one to study complex biological samples directly in solution. Moreover, in recent years, nanodiscs (NDs), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type CBS-PPases, including dhPPase, are homotetrameric [19,20]. The deletion variant, which lacked the catalytic DHHA2 domain, retained the tetrameric structure, as demonstrated by two different approaches-size-exclusion chromatography and analytical ultracentrifugation.…”
Section: Oligomeric Structure Of ∆Dhppasementioning
confidence: 99%
“…The first proposed model of the entire CBS-PPase molecule based on these structures also assumed that it is homodimeric [18]. However, more recent studies have demonstrated that CBS-PPase is tetrameric [19,20]. We have subsequently proposed two possible structural models of the domain organization in tetramers [19], but neither of them has been verified experimentally.…”
Section: Introductionmentioning
confidence: 99%